Pengelolaan Zakat Produktif LAZNAS Al-Azhar untuk Pemberdayaan Dhuafa Melalui program Rumah Gemilang Indonesia - Farah Dianti Safira; Suherman Rosyidi (Universitas Airlangga, 2019)
The background of this research is the existence of unemployed and poverity phenomenon. This phenomenon encourages researchers to take research that discusses about productive zakat management of national zakat institution of Al-Azhar, through Rumah Gemilang Indonesia as the solution. This research uses qualitative approach with case study strategy. Data collection is done through interviewing techniques with related parties and the documents concerned. Analytical techniques carried out in this research is the technique of source triangulation and descriptive qualitative analysis techniques.The results of this study indicate that the national zakat institution of Al-Azhar recieves funds from the donors. They distributed the funds to Rumah Gemilang Indonesia as one of their programs, that aims to empower the dhuafas through six months training with no charge of tuition fee. So the dhuafas can be freed from unemployed and poverty problems.Keywords: productive zakat management, national zakat institution, empowerment, dhuafaREFERENCES Nasution, Mustafa Edwin dkk. 2006. Pengenalan Ekslusif Ekonomi Islam. Jakarta: Prenadamedia Grup.Qadir, Abdurrachman. 2001. Zakat (Dalam Dimensi Mahdah dan Sosial). Jakarta: PT Raja Grafindo Persada.Wibisono, Yusuf. 2015. M.engelola Zakat Indonesia. Jakarta: Prenadamedia Group.Yin, Robert K. 2002. Studi Kasus Desain dan Metode. Jakarta: PT Raja Grafindo Persada.